Expressive Speech Act In Andung-Andung Batak Toba - Michelle Devina Pasaribu; Mangatur Sinaga; Charlina (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research is a type of qualitative descriptive research entitled Expressive Speech Acts in Andung-Andung Batak Toba. This study describes the form and function of expressive speech acts in andung-andung speech. The data of this study are language units in the form of words, phrases, clauses or sentences of andung-andung in 9 YouTube channels and 7 amateur videos. The data sources of this study are YouTube channels and amateur videos. Based on the research findings, it is known that there are 2 forms of speech acts, namely direct literal speech acts and direct non-literal speech acts. The functions of expressive speech acts are six, namely (1) thank you, (2) congratulate, (3) hope, (4) apologize, (5) praise, (6) expression. Speech act data based on the forms that have been found, the most dominant direct literal speech act because this andung-andung tradition is spoken by the speaker to the speech partner directly using language that has meaning according to its true meaning (literal meaning). Expressive speech act data based on its functions that have been found, the most dominant expressive function of expressing sadness among other expressive functions. The function of expressing sadness becomes the dominant expressive function because andung-andung is a speech that contains lamentations and sentences that express a person's sadness.